2015
DOI: 10.15850/amj.v2n2.549
|View full text |Cite
|
Sign up to set email alerts
|

Dermatomycosis among Elementary School Children in Jatinangor West Java

Abstract: Background: Dermatomycosis often occurs in tropical countries. Many studies from tropical countries have reported high prevalence of dermatomycosis among elementary school children. Despite being a tropical country, prevalence of dermatomycosis among elementary school children in Indonesia is still unknown. The objective of this study was to determine the prevalence and characteristics of dermatomycosis among elementary school children in Jatinangor, Sumedang, West Java in September-November 2012. Methods: Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…3 Studies have found that of all the dermatological cases studied; there is a 20% occurrence of dermatomycosis with conditions due to dermatophyte infections as the most seen at 11.4%. 4 A further statistical breakdown provided by studies that have been published shows that tinea capitis itself is highly common to those of 6-10 years of age, school-attending and prepubertal.…”
Section: Introductionmentioning
confidence: 99%
“…3 Studies have found that of all the dermatological cases studied; there is a 20% occurrence of dermatomycosis with conditions due to dermatophyte infections as the most seen at 11.4%. 4 A further statistical breakdown provided by studies that have been published shows that tinea capitis itself is highly common to those of 6-10 years of age, school-attending and prepubertal.…”
Section: Introductionmentioning
confidence: 99%